Reformasi Administrasi dan Karakter Bangsa : Sebuah Kajian Konseptual - Bambang Irawan (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
Administrative reform is basically an administrative process improvements on an ongoing basis. As a process, administrative reform has certain goals to be achieved. On the other hand, the character of the nation's understanding of transformation born of cultural values in society can serve as the foundation for the direction of administrative reform a nation. It's intended as a bridge in understanding the interconnection between both concepts.